2023
DOI: 10.54504/1684-6753-2023-1-70-100
|View full text |Cite
|
Sign up to set email alerts
|

Headache during pregnancy

Abstract: Headaches are a common neurological complaint during pregnancy. Most are primary and benign but secondary headaches may also occur. In the first trimester, the complaints are mainly due to primary headaches, and in the last trimester, the proportion of secondary headaches increases. This article provides clinical characteristics of secondary headaches during pregnancy. The limited range of drugs that can be used during pregnancy, in the absence of potential adverse effects on the mother and fetus/newborn, caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
0
0
Order By: Relevance
“…The results underline the significant prevalence of headaches among pregnant women, with approximately 246 (59.9%) reporting this condition before and during pregnancy. This aligns with previous studies highlighting the high prevalence of headaches during pregnancy [18][19][20][21]. This emphasizes the crucial role of healthcare professionals in paying attention to complaints about headaches during prenatal visits.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results underline the significant prevalence of headaches among pregnant women, with approximately 246 (59.9%) reporting this condition before and during pregnancy. This aligns with previous studies highlighting the high prevalence of headaches during pregnancy [18][19][20][21]. This emphasizes the crucial role of healthcare professionals in paying attention to complaints about headaches during prenatal visits.…”
Section: Discussionsupporting
confidence: 91%
“…This emphasizes the crucial role of healthcare professionals in paying attention to complaints about headaches during prenatal visits. Headaches during pregnancy can be attributed to various factors, such as primary and secondary headaches, hormonal changes, stress, dehydration, and insufficient sleep [20][21][22]. A detailed analysis of headache characteristics before pregnancy revealed that most headaches were undiagnosed 211 (51.3%), stressing the importance of accurate headache diagnosis before pregnancy [12,23].…”
Section: Discussionmentioning
confidence: 99%